Kriteria planlet kelapa kopyor yang siap untuk diaklimatisasi [Criteria of kopyor coconut plantlets ready to be acclimatized] - . SUMARYONO; Imron RIYADI (Menara Perkebunan, 2016)
Kopyor coconut is a special coconut grown in Indonesia. Nuts of kopyor can not be used as a source of planting material due to its endosperm damage; therefore in vitro embryo rescue technique is applied to propagate kopyor coconuts. Acclimatization is a critical stage during in vitro culture of kopyor coconut. Experiments were conducted to determine the effect of plantlet initial conditions prior to acclimatization on survival and growth in ex vitro conditions. Five replications of 50 plantlets of tall variety of kopyor coconut with different shoot and root conditions were used in the acclimatization process. The coconut plantlets were planted on plastic pots containing a mixture of soil, sand and dung manure, and then placed inside a closed plastic tunnel.  The tunnel was opened gradually after 3 months and the plants were transferred to the nursery after 4.5 months. Survival frequency and growth (plant height, leaf number and shoot diameter) of the plantlets were observed after 6 months of acclimatization period. Research results show that the initial plantlet height and initial root length affected significantly the survival rate and growth of the plantlets of kopyor coconut during acclimatization. Other parameters of plantlet initial conditions such as leaf number, stem diameter, primary root number, and the existence of secondary roots did not influence the survival rate and growth of the plantlets.  In order to obtain high survival rate (84.7%) and good growth of plantlets during acclimatization, the plantlet height must be at least 20 cm prior to acclimatization.  Differences in root length on plantlets with the height of 20 cm or more, did not affect survival percentage of the vitroplants.